The health benefits of autonomous vehicles: public awareness and receptivity in Australia - Pettigrew, Simone; Talati, Zenobia; Norman, Richard (Wiley-Blackwell Publishing Asia, 2018)
Objectives: The substantial public health benefits of autonomous vehicles will be optimised once all vehicles operate in autonomous mode. This form of disruptive technology will need to be widely accepted by the community to facilitate the regulatory and behavioural adjustments required to achieve rapid adoption. The aim of this study was to assess: i) receptiveness to autonomous vehicles; ii) the salience of various health benefits (e.g. crash prevention, emission reduction, driving stress reduction, cyclist safety, increased mobility for those unable to drive); and iii) prompted awareness of these health benefits. Methods: Quantitative and qualitative data were generated via a national online survey of a broad range of Australians aged 16 years and over (n=1,624). Results: There were neutral levels of receptiveness and very low salience of health benefits, but more substantial levels of prompted awareness of positive health outcomes. Conclusions: These results suggest that the public may be interested in information relating to the individual and societal health benefits of autonomous vehicles, which in turn may increase overall support for this innovation. Implications for public health: Australians are likely to be receptive to autonomous vehicles when provided with information relating to their public health benefits.